CT‐Guided Wire Localization for Involved Axillary Lymph Nodes After Neo‐adjuvant Chemotherapy in Patients With Initially Node‐Positive Breast Cancer. Issue 4 (9th April 2016) - Trinh, Long; Miyake, Kanae K.; Dirbas, Frederick M.; Kothary, Nishita; Horst, Kathleen C.; Lipson, Jafi A.; Carpenter, Catherine; Thompson, Atalie C.; Ikeda, Debra M.
Abstract: Resection of biopsy‐proven involved axillary lymph nodes (iALNs) is important to reduce the false‐negative rates of sentinel lymph node (SLN) biopsy after neo‐adjuvant chemotherapy (NAC) in patients with initially node‐positive breast cancer. Preoperative wire localization for iALNs marked with clips placed during biopsy is a technique that may help the removal of iALNs after NAC. However, ultrasound (US)‐guided localization is often difficult because the clips cannot always be reliably visible on US. Computed tomography (CT)‐guided wire localization can be used; however, to date there have been no reports on CT‐guided wire localization for iALNs. The aim of this study was to describe a series of patients who received CT‐guided wire localization for iALN removal after NAC and to evaluate the feasibility of this technique. We retrospectively analyzed five women with initially node‐positive breast cancer (age, 41–52 years) who were scheduled for SLN biopsy after NAC and received preoperative CT‐guided wire localization for iALNs. CT visualized all the clips that were not identified on post‐NAC US. The wire tip was deployed beyond or at the target, with the shortest distance between the wire and the index clip ranging from 0 to 2.5 mm. The total procedure time was 21–38 minutes with good patient tolerance and no complications. In four of five cases, CT wire localization aided in identification and resection of iALNs that were not identified with lymphatic mapping. Residual nodal disease was confirmed in two cases: both had residual disease in wire‐localized lymph nodes in addition to SLNs. Although further studies with more cases are required, our results suggest that CT‐guided wire localization for iALNs is a feasible technique that facilitates identification and removal of the iALNs as part of SLN biopsy after NAC in situations where US localization is unsuccessful.